The impact of isometric exercises on correcting upper body muscle imbalances in young elite badminton players - Gasibat, Qais; Abdullah, Borhannudin; Samsudin, Shamsulariffin; Elsharief, Abdusalam; Alexe, Cristina Ioana; Anghel, Mihaela; Alexe, Dan Iulian (Montenegrin Sports Academy, 2025)
Overhead athletes are at a higher risk of injury when the internal rotation strength of their dominant shoulder exceeds that of the non-dominant shoulder by 9%, and the external rotation strength is 14% greater in the dominant shoulder compared to the non-dominant shoulder.Though 15% of bilateral strength difference is recognized in the literature as an imbalance. This study examined the effect of isometric exercise on muscle imbalance in young elite badminton players. The study was conducted using an experimental design with pre-test and post-test methodologies. We included approximately 80 Malaysian elite badminton players, comprising 42 male and 38 females, with an average age of 15 years and a maturity level of 2.05 peak height velocity. Participants were randomly assigned to two groups. The experimental group followed a 12-week internal and external rotation isometric exercise regimen. Three key measurements were taken during the study: pre-test data collected before any intervention, post-test1 data after 4 weeks of isometric exercises (12 sessions), and post-test2 data after 12 weeks of isometric exercises (36 sessions). A MicroFET®2 digital handheld dynamometer was used to assess muscle imbalance, focusing on the internal and external rotations of the dominant and non-dominant shoulders. The results showed a significant improvement in the muscle imbalance of the experimental group. Post-tests 1 and 2 revealed considerable improvements in the muscle imbalance ratios (p<0.01Ƞ = 0.791, 0.807). Isometric exercises were found to significantly influence muscle imbalance (p<0.01; Ƞ = 0.769). This study established a positive and significant interaction between isometric exercise repetitions and muscle imbalance within the experimental group. Overall, the findings concluded that isometric exercises can significantly decrease muscle imbalance, with positive and significant effects observed even after just 4 weeks of the intervention in the treatment group.